2006
DOI: 10.1007/s11244-006-0081-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of catalyst film thickness on the magnitude of the electrochemical promotion of catalytic reactions

Abstract: The effect of catalyst film thickness on the magnitude of the effect of electrochemical promotion was investigated for the model catalytic reaction of C 2 H 4 oxidation on porous Pt paste catalyst-electrodes deposited on YSZ. It was found that the catalytic rate enhancement q is up to 400 for thinner (0.2 lm) Pt films (40,000% rate enhancement) and gradually decreases to 50 for thicker (1 lm) films. The Faradaic efficiency L was found to increase moderately with increasing film thickness and to be described se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…7. This behaviour was already reported by Koutsodontis et al [28] and was attributed to the decrease in amount of promoter on the gas exposed catalyst surface due to the reaction of O d-with the hydrocarbons in good agreement with a developed mathematical model.…”
Section: Catalytic Activity Measurements Under Open-circuitsupporting
confidence: 88%
“…7. This behaviour was already reported by Koutsodontis et al [28] and was attributed to the decrease in amount of promoter on the gas exposed catalyst surface due to the reaction of O d-with the hydrocarbons in good agreement with a developed mathematical model.…”
Section: Catalytic Activity Measurements Under Open-circuitsupporting
confidence: 88%
“…This behaviour is expected, as in this system by increasing the oxygen partial pressure in the reaction chamber we decrease the oxygen chemical potential difference across the membrane and thus the driving force for oxygen migration that consequently affects the promoter supply to the catalyst. While for classic EPOC high rate enhancement ratios of ethylene oxidation on platinum have generally been reported under highly oxidising conditions [16], in the case of wireless EPOC higher rate enhancement ratios have so far been obtained under stoichiometric or mildly oxidising conditions [12,14]. Work is currently in progress to study wireless EPOC under reducing conditions (i.e.…”
Section: Kinetic Data Analysismentioning
confidence: 99%
“…Besides the results which have been already reported in the literature till 2001 and reviewed by Professor Vayenas et al in the ''Electrochemical Promotion of Catalysis'' book [28] several new studies have been reported till the end of 2008 using various techniques and methods such as TPD [29,30,32,47,72], TPR [29], CV [21], FTIR [21], SEM-EDX [21], AC impedance spectroscopy [39], STM [73,74], work function measurements and theoretical considerations [18,75,76], transients experiments and kinetic studies [34,35], quantum mechanical calculations and Monte Carlo simulations [77] and general thermodynamic considerations [18,78,79]. The use of oxygen temperature programmed desorption both under UHV and atmospheric pressure conditions has proven [29,30] the existence of two different and distinct oxygen adsorption states on the catalyst surface when oxygen ion conductors used like YSZ.…”
Section: Electrochemical Promotion Of Reactions With Environmental Anmentioning
confidence: 99%
“…K values up to 3 9 10 5 and q values up to 150 [28] have been found for several systems. More recently q values between 300 [34,35] and 1,400 [36,37] have been observed for C 2 H 4 and C 3 H 8 oxidation on Pt/YSZ, respectively. In the experiment of Fig.…”
Section: Introductionmentioning
confidence: 97%